Neuroeducation and Artistic Expression. An Overview from the Biopsychology Viewpoint - Halkiopoulos, C; Gkintoni, E; Antonopoulou, H (Technium Education and Humanities, 2023)
In this research, the relationship between positive emotions and the pathways that govern how artistic concepts are processed in the brain and influence the essential characteristics of learning - focus, memory, and motivation - is investigated. In addition, the brain mechanisms of emotional and cognitive links are investigated in order to give a framework for the present discoveries of neuroscience in order to elucidate the relationship between emotions and cognition. The relationship between emotions and art and artistic activities in general is then established, and its contribution to the educational process is emphasized. In conclusion, the fundamental principles of neuroaesthetics and neuroimaging for this topic are studied, and therapeutic effects of artistic activities are discussed.